1996
DOI: 10.3109/02652049609026015
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal formulations containing sodium mercaptoundecahydrododecaborate (BSH) for boron neutron capture therapy

Abstract: Sodium mercaptoundecahydrododecaborate or BSH is a compound most widely used for boron neutron capture therapy (BNCT). Liposome formulations containing BSH, with or without steric stabilization, were prepared as potential agents for delivery of boron compounds for BNCT. Liposomes composed of DPPC/CHOL in a molar ratio 1:1 (PEG concentration: 5 mol%) were prepared having an average diameter in the range of 100-110 nm 200 mu L of liposomes (l.88 mg phospholipid/mouse and 3.5-5.8 mg BSH/kg body weight) were injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 21 publications
0
28
2
Order By: Relevance
“…Target compounds II and III were obtained in a similar fashion, and yields for all three target compounds ranged from 46% to 56%. All intermediates and target compounds were purified effectively by silica gel column chromatography and characterized by 1 H NMR, 13 C NMR, and HR-EIMS. An important criterion for the synthesis of compounds I-III was practicability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Target compounds II and III were obtained in a similar fashion, and yields for all three target compounds ranged from 46% to 56%. All intermediates and target compounds were purified effectively by silica gel column chromatography and characterized by 1 H NMR, 13 C NMR, and HR-EIMS. An important criterion for the synthesis of compounds I-III was practicability.…”
Section: Resultsmentioning
confidence: 99%
“…Purification by silica gel flash chromatography (hexanes/ethylacetate 8:2; R f : 0.4) gave II in 50% yield. 1 13 RMS Fit of Cholesterol with Compounds I-III ( Figure 2). Hyperchem 7.51 (Hypercube, Inc., Gainsville, FL) was used on a Dell Inspiron 4100 to produce the rms fit of cholesterol with the carboranyl cholesterol mimics I-III.…”
Section: -(4-hydroxyphenyl)-7-(6-methylheptyl)-17-dicarba-closododementioning
confidence: 99%
“…23 In particular, poly(ethylene glycol) (PEG)-modified liposomes encapsulating BSH in their interior have attracted attention as effective nano-sized carriers of 10 B atoms because of their biocompatibility, long blood-circulation time and effective accumulation in tumors through EPR effects. 24 Maruyama et al prepared a transferrin-conjugated PEG-modified liposome encapsulating BSH to enhance the specificity of the liposome against tumors [25][26][27] because it is well-known that the transferrin receptor concentration on tumor cells is much higher than that on normal cells. 28 Although the PEGmodified liposomes encapsulating BSH showed higher accumulation in the tumor region than free BSH through the EPR effect, the therapeutic efficacy of the BSH-encapsulated liposomes remains controversial because of the leakage of the encapsulated BSH from the liposome into the blood stream caused by the high ion osmotic pressure of the BSH-loaded interior of the liposome.…”
Section: Introductionmentioning
confidence: 99%
“…An advanced pharmaceutical formulation of a boron compound administered directly to the tumor site within the brain parenchyma bypasses the BBB, elevates local B 10 concentration, and assures that normal tissues in the rest of the body will not be exposed to the cytotoxic products of radiation. Liposomes offer an advantage over other formulations because they can carry relatively large quantities of therapeutic agents and facilitate their delivery to cells (Mehta, Lai, and Lu 1996). Our early study showed that intracerebral injection of liposomes containing borocaptate (BSH), a boron cage compound (Figure 1), was safe (Mehta, Olson, and Lu 1995).…”
mentioning
confidence: 99%